2022
DOI: 10.17066/tpdrd.1138253
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness in Teaching and Positive Characteristics in Teachers: Prosocial Behaviors as Mediator

Abstract: Öğretmenlerin, bireylerin gelişimleri üzerindeki etkilerinin önemi sıklıkla vurgulanmakta; pozitif öğretmen özelliklerinin hem öğretmenler hem de öğrenciler üzerindeki olumlu etkileri kabul edilmektedir. Ancak pozitif öğretmen özelliklerinde etkili olan değişkenlere yönelik çalışmaların ağırlıklı olarak kişi-içi psikolojik süreçlerle ilgilendiği görülmektedir. Bu nedenle pozitif öğretmen özelliklerinde etkili olabilecek değişkenlerin kişilerarası ve eğitim ortamı bağlamında ele alınmasının pozitif öğretmen öze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…For example, in a study conducted in Iran, it was found that positive teacher characteristics are also valid for Iranian culture (Dezaki, Nadi & Sajjadian, 2022). In another study, the relationships between mindfulness-based teaching and positive teacher characteristics were examined (Gördesli & Örnek, 2022). Similarly, another study investigated positive teacher characteristics to help students with learning difficulties (Oğuz et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study conducted in Iran, it was found that positive teacher characteristics are also valid for Iranian culture (Dezaki, Nadi & Sajjadian, 2022). In another study, the relationships between mindfulness-based teaching and positive teacher characteristics were examined (Gördesli & Örnek, 2022). Similarly, another study investigated positive teacher characteristics to help students with learning difficulties (Oğuz et al, 2020).…”
Section: Discussionmentioning
confidence: 99%